Hubungan Antara Self-Compassion dan Efikasi Diri pada Mahasiswa yang Sedang Menyelesaikan Tugas Akhir - Siswati, Siswati; Hadiyati, Frieda Nuzulia Ratna (Mediapsi, 2017)
Students as late adolescents often experience unstable physical and emotional conditions due to suffering they endure. It then affects his efficacy. Self-acceptance is necessary when facing suffering and difficult situations in life. This research aims to determine empirically the relationship between self-compassion and self-efficacy among students who are completing their final project. This research employed a quantitative method with correlational design. The measuring tool used in this research was The Self-Compassion Scale consisting of 22 items (Î±=0.858) and Self-Efficacy Scale with 22 items (Î±=0.850). The subjects of this research were 110 third-year students on Faculty of Psychology University Y, obtained by simple random sampling technique. Data obtained from this research was then analyzed by using simple regression analysis technique. The result showed the correlation coefficient of 0.741 with p=0.000 (p<0.05), meaning that alternative hypothesis proposed by the researcher was accepted. Determinant coefficient value of self-compassion gave an effective contribution of 54.9% for self-efficacy variable, while the remaining 45.1% is affected by other unrevealed factors.Mahasiswa sebagai remaja akhir sering kali mengalami kondisi fisik dan emosi yang tidak stabil dikarenakan penderitaan yang dialaminya. Hal tersebut selanjutnya berdampak pada efikasi dirinya. Penerimaan diri diperlukan ketika menghadapi penderitaan dan situasi sulit dalam kehidupan. Penelitian ini bertujuan untuk mengetahui secara empiris hubungan antara self-compassion dan efikasi diri pada mahasiswa yang sedang menyelesaikan tugas akhir. Penelitian ini menggunakan metode kuantitatif dengan rancangan korelasional. Alat ukur yang digunakan adalah Skala Self-Compassion yang berjumlah 22 butir (Î±=0.858) dan Skala Efikasi Diri yang berjumlah 22 butir (Î±=0.850). Subjek penelitian adalah mahasiswa semester 6 Fakultas Psikologi Universitas Y berjumlah 110 orang yang diperoleh melalui teknik simple random sampling. Teknik analisis data yang digunakan yaitu teknik analisis regresi sederhana. Berdasarkan hasil analisis data yang dilakukan diperoleh koefisien korelasi sebesar 0.741 dengan p=0.000 (p<0.05). Artinya, hipotesis alternatif yang diajukan peneliti dapat diterima. Nilai koefisien determinan self-compassion memberikan sumbangan efektif sebesar 54.9% untuk variabel efikasi diri, sedangkan 45.1% sisanya dipengaruhi oleh faktor-faktor lain yang tidak diungkap dalam penelitian.